Danau Sentarum national park: the abandoned paradise (Center for International Forestry Research, 2005)
Danau (Lake) Sentarum is one the most unique wetlands in Asia, marked by outstanding biodiversity. This area was declared as a national park in 1999, covering 132,000 hectares. The park is located in the upper Kapuas district, which declared itself a conservation district in 2003. What’s the current condition of the park? Who manages and who owns it? And how’s the condition of the people who have been living in this area for hundreds of years? This movie is dedicated to the local people of Danau Sentarum and to those who are trying to save it. Establishment of the national park and the conservation district requires some supporting conditions to achieve the goals.